European Regulations for Labeling Requirements for Food Allergens and Substances Causing Intolerances: History and Future. (23rd November 2019) - Koeberl, Martina; Clarke, Dean; Allen, Katrina J; Fleming, Fiona; Katzer, Lisa; Lee, N Alice; Lopata, Andreas L; Said, Maria; Scheelings, Pieter; Shepherd, Neil; Sherlock, Robin; Roberts, James
Abstract: Food allergies are increasing globally, including numbers of allergens, the sensitization rate, and the prevalence rate. To protect food-allergic individuals in the community, food allergies need to be appropriately managed. This paper describes current Australian food allergen management practices. In Australia, the prevalence of food allergies, the anaphylaxis rate, and the fatal anaphylaxis rate are among the highest in the world. Interagency and stakeholder collaboration is facilitated and enhanced as Australia moves through past, current, and ongoing food allergen challenges. As a result, Australia has been a global leader in regulating the labeling of common allergens in packaged foods and their disclosure in foods not required to bear a label. Moreover, the food industry in Australia and New Zealand has developed a unique food allergen risk management tool, the Voluntary Incidental Trace Allergen Labelling program, which is managed by the Allergen Bureau. This paper summarizes insights and information provided by the major stakeholders involved to protect food-allergic consumers from any allergic reaction. Stakeholders include government; consumer protection, regulation, and enforcement agencies; the food industry; and food allergen testing and food allergen/allergy research bodies in Australia. The ongoing goal of all stakeholders in food allergen management in Australia is to promote best practice food allergen management procedures and provide a wide choice of foods, while enabling allergic consumers to manage their food allergies and reduce the risk of an allergic reaction.